A Study on Secondary School Students' Problem Solving Strategies - HANGÜL, TUĞBA (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2015)
The aim of this study is to determine 6th grade students' use of problem solving strategies and difficulties that they have in this process. This research has been done by the help of the 12 6th grade public school students who were attending a public school in the 2012-2013 academic year. The data collection tools for the research consisted of problem tests, including 7 problems which have taken from PISA and some mathematics websites. Each problem was chosen involving only a single strategy. The obtained data was analyzed utilizing descriptive analysis and descriptive statistics. According to the results of the study, all of the students who participated in the study solve the problems about Look for a Pattern, Start at the End, Use an Equation and Make an Organized List strategies. Two students could not solve problems including Draw a Diagram and Divide and Conquer strategies. Also, three students could not solve the problem about Guess and Check. In addition, findings of this study show that some texts of problems are long and complex for students. On the other hand, students had some difficulties when they used the strategy of Guess and Check and they spent a lot of time on the problem about Divide and Conquer.
Keywords: Mathematics; Secondary school students; Problem-solving steps; Problem-solving strategies